Environmental exposures and human health challenges - Papadopoulou, Paraskevi, 1961-; Marouli, Christina, 1961-; Misseyanni, Anastasia, 1962- (Advances in human services and public health book series., 2019)
"This book examines in a cross-cutting coverage, how various environmental exposures affect individuals, workers, professions, and populations from different regions of the world. It also addresses concepts and theories related to environmental exposures and human health impacts via the air, water, soil, heavy metal exposure, and other chemical toxins including exposure to radiation and use of pesticides"--Provided by publisher